ANALISIS KEMAMPUAN PASSING BAWAH BOLA VOLI PADA KEGIATAN EKSTRAKURIKULER SISWA KELAS VIII SMP N 1 MUARO JAMBI - Yoral Zaputra; Atri Widowati; Bangkit Yudho Prabowo (LPPM STAI Muhammadiyah Probolinggo, 2025)
Based on the researcher's observations at SMP Negeri 1 Muaro Jambi, particularly among eighth-grade students, it was found that during physical education classes, students' passing skills were not yet optimal. When performing passing movements, the coordination between foot and hand movements was still unbalanced, causing the ball to frequently miss the intended target. Therefore, through this study, the researcher aims to specifically examine the students' skills, with the hope that errors in movement can be evaluated and improved. The purpose of this study is to determine the underhand passing ability in volleyball during extracurricular activities among eighth-grade male students at SMP Negeri 1 Muaro Jambi. This research is a survey study using a quantitative descriptive method, employing tests and measurement techniques to collect data. This approach provides a numerical representation of the research findings, measured precisely. The sample in this study was selected using a total sampling technique, considering various factors mentioned earlier. Thus, the subjects of this research were 12 eighth-grade students participating in extracurricular activities at SMP Negeri 1 Muaro Jambi. Based on data analysis, the results of the underhand passing ability test showed that out of 12 students, 5 students (41.67%) were categorized as